2012
DOI: 10.1103/physrevd.86.054007
|View full text |Cite
|
Sign up to set email alerts
|

Polyakov loop and gluon quasiparticles in Yang-Mills thermodynamics

Abstract: We study the interpretation of lattice data about the thermodynamics of the deconfinement phase of SUð3Þ Yang-Mills theory, in terms of gluon quasiparticles propagating in a background of a Polyakov loop. A potential for the Polyakov loop, inspired by the strong coupling expansion of the QCD action, is introduced; the Polyakov loop is coupled to transverse gluon quasiparticles by means of a gaslike effective potential. This study is useful to identify the effective degrees of freedom propagating in the gluon m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 75 publications
3
31
0
Order By: Relevance
“…T c [39]. It is worth mentioning that in a recent work [40], it has been shown that the inclusion of a Polyakov loop dynamics leads to a gluon mass with a very smooth dependence on T. From HTL calculations, it is expected that at very high T, m g ðTÞ $ ffiffiffiffiffiffiffiffiffiffiffiffi ffi S ðTÞ p T [6,38], with a quasilinear behavior for T * 2 T c . This is not the case in our model since our ansatz for the gluon mass is not inspired from HTL theory but is instead completely driven-with no freedom-by data from Ref.…”
Section: A Potential and Gluon Massmentioning
confidence: 98%
“…T c [39]. It is worth mentioning that in a recent work [40], it has been shown that the inclusion of a Polyakov loop dynamics leads to a gluon mass with a very smooth dependence on T. From HTL calculations, it is expected that at very high T, m g ðTÞ $ ffiffiffiffiffiffiffiffiffiffiffiffi ffi S ðTÞ p T [6,38], with a quasilinear behavior for T * 2 T c . This is not the case in our model since our ansatz for the gluon mass is not inspired from HTL theory but is instead completely driven-with no freedom-by data from Ref.…”
Section: A Potential and Gluon Massmentioning
confidence: 98%
“…Therefore, to investigate the robustness of nonlocal PNJL models, one can modify the choice of the Polyakov-loop potential, for instance taking into account developments made in Refs. [39][40][41] or rather general prescriptions as in Refs. [42,43].…”
Section: T − μ Phase Diagrammentioning
confidence: 99%
“…It is worth to mention that there have been other quasiparticle descriptions in the literature, which could be characterized as effective mass models [66][67][68][69], effective mass models with gluon condensate [70][71][72][73], and effective models with a Polyakov loop [74][75][76][77][78][79][80]. The effective model with a Polyakov loop in [80] has been thermodynamically consistent.…”
Section: Near (Non)-equilibrium Quark and Gluon Distributionsmentioning
confidence: 99%